RESI LARAS GAMELAN CRAFTSMEN IN PHOTOGRAPHIC ESSAY - Fatoni, Azizul Karim; Prakoso, Priaji Iman (Institut Seni Indoensia Surakarta, 2025)
The work titled “Gamelan Craftsmen of Resi Laras in a Photography Essay” aims to visualize the gamelan-making process in Karanganyar Regency through a photographic essay and to explore appropriate lighting arrangements for this process. The subject of this work includes gamelan craftsmen in the process of gamelan-making, from intial to the final stages. The creative method involved several stages: data collection, exploration, experimentation, producting, editing, and presentation. The resulting work consist of 20 photographs measuring 60x90cm. This work is expected to serve as a visual archive for preserving gamelan crafts and provide insight to the public about Gamelan Resi Laras-making process and provide references for essay photography.